2017
DOI: 10.1002/cssc.201601685
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Energy Catalytic Electrolysis for Simultaneous Hydrogen Evolution and Lignin Depolymerization

Abstract: Here, a new proton-exchange-membrane electrolysis is presented, in which lignin was used as the hydrogen source at the anode for hydrogen production. Either polyoxometalate (POM) or FeCl was used as the catalyst and charge-transfer agent at the anode. Over 90 % Faraday efficiency was achieved. In a thermal-insulation reactor, the heat energy could be maintained at a very low level for continuous operation. Compared to the best alkaline-water electrolysis reported in literature, the electrical-energy consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…Another important result was the onset voltage of ca . 0.25 V at all the tested temperatures, which was comparable to those reported for direct ethanol electrolysis, and much lower than those reported for indirect lignin electrolysis . Figure (b) shows hydrogen evolution rates from the cathode at various temperatures, including the theoretical values calculated using Faraday's law, based on the two‐electron reaction represented in Reaction (4).…”
Section: Figuresupporting
confidence: 69%
“…Another important result was the onset voltage of ca . 0.25 V at all the tested temperatures, which was comparable to those reported for direct ethanol electrolysis, and much lower than those reported for indirect lignin electrolysis . Figure (b) shows hydrogen evolution rates from the cathode at various temperatures, including the theoretical values calculated using Faraday's law, based on the two‐electron reaction represented in Reaction (4).…”
Section: Figuresupporting
confidence: 69%
“…C1 (CÀCo rC ÀH) arise mainly because of lignin and extractives, C2 (CÀO) and C3 (C=O) are the predominant linkages in cellulose, and holocellulosew as rich in C2 and O2. [51] The proportion of CÀO and C=Ob onds increased and the proportion of C=C( or CÀC) bonds decreaseda fter the pretreatment, which may be because of the oxidation of CÀC( or C=C) bonds on the surface to CÀOa nd C=Ob onds by FeCl 3 /NaNO 3 . The O1sp eaks for HW and SW were also deconvoluted into three categories:O 1( C =O), O2 (CÀO), and O3 (O=CÀOR).…”
Section: Investigation On Properties Of Untreated and Pretreated Woodsmentioning
confidence: 97%
“…[160] Amaximum hydrogen production rate of 0.45 mmol s À1 was obtained. Du et al [140] reported the simultaneous electrooxidation of Kraft lignin to value-addedc hemicals at ag raphite-felt anode and the cogeneration of hydrogen gas at aP t/graphite cathode in ap rotone xchange membrane (PEM) electrochemical cell using ap olyoxometalate (POM) phosphomolybdic acid (H 3 PMo 12 O 40 denoted as PMo 12 )o rF eCl 3 as catalyst and chargetransfer mediators. For both POM and FeCl 3 ,o ver 90 %c urrent efficiency was reported while the energy consumption was re-duced by 40 %i nc omparison to the best reported PEM electrolysis energy consumption.…”
Section: Electrochemical Degradation Of Lignin For Hydrogen Co-producmentioning
confidence: 99%
“…at 100 8Ca fter 18 h. Increasing the temperature to 190 8C for 1h resulted in 26.6 %o ft he solid lignin being oxidized to low-molecular-weight compounds. [140] NaderiNasrabadi et al developed ae lectrolyzer for biomass depolarization that can electrooxidize lignin-rich biorefinery waste to produce high-purity (97.6 %) hydrogen gas at mild conditions (room temperaturea nd atmosphericp ressure) using Ni-Co/TiO 2 on carbon paper anode. [161] At ap otential lower than 1.5 V, regardless of the temperature, lignin oxidation was thermodynamically favored over the OER whilea bove 1.5 VO ER was kinetically easier to achievet han lignin oxidation.…”
Section: Electrochemical Degradation Of Lignin For Hydrogen Co-producmentioning
confidence: 99%